Concept Understanding Level of Junior High School Students on Substance Pressure Material - Devi Safitri Kafulillah; Septi Budi Sartika (Universitas Pendidikan Ganesha, 2023)
Low concept understanding on students can cause students to experience difficulties in learning certain materials. To overcome this, it is necessary to identify understanding of the concept in students using the right method. This research aims to analyze the level of students' concept understanding using the five tier test method on substance pressure material. This research uses a quantitative approach with a survey type of research. The subjects in this research were students in 8th and 9th grade totalling 716 students. The sample used was students who had received substance pressure material consisting of 258 students. The instrument used a five tier test. Based on the results of the research, it can be seen that the percentage of understanding of the concept of the students for each indicator and sub concept of substance pressure is 16%, so it can be concluded that the level of understanding of the concept of substance pressure in students using the five-tier test method is included in the low criteria. Future research is expected to develop this research again, so that later it can be used as a reference for teachers in determining the right learning strategy to improve students' understanding of the concept of substance pressure.